住宅団地の住環境形成過程における合意形成システムに関する研究 - 河辺 聡; 西村 征一郎; 森田 孝夫; 鈴木 克彦 (住宅総合研究財団研究年報, 1990)
A building agreement can be considered a social institution for managing a living environment by the people in a local community. Building agreements fall into two classes: “agreement by all parties concerned,” concluded on the initiative of the people living in the community, and “agreement not requiring consent of the people living in the community,” which the builder has concluded prior to the sale of the property. The large majority of building agreements are agreements not requiring the agreement of the people living in the community. Because of this situation, various problems have arisen in these communities over the operation of building agreements. At the same time, it is necessary to examine measures for operating the building agreements over a long period of time. The objective of this study is to examine methods of consensus building, and improve upon the problem areas of building agreements and make effective the functions of housing environment building through neighborhood participation. With these objectives in mind, we have clarified the actual conditions of the operation of building agreement at housing developments where the housing environment has been on its way to maturity. Furthermore, in this research, the actual state of the activities of the people living in the neighborhood for concluding a building agreement after securing the consensus was surveyed. Finally, in this study, the basic conditions were examined for promoting consensus building from the results of the above study. From the finding of the survey, it was found that, even in areas where the building agreements had been concluded by the builders, agreements in many of the communities had been renewed with the neighborhood people placing high evaluation on the building agreements. It was further clarified that various measures were established according to the actual status of the communities by varying the contents and areas subject to the agreements. At the same time, it was found that the activities for building consensus for a certain building agreement varied according to the reasons why the building agreement was concluded or according to environmental conditions of the community. Furthermore, it was found that the building agreement played an important role in forming the norms but a large amount of time was required for procedures to secure consensus. At the same time, it's made clear that the uniformity in the housing environment and the existence of a normative attitude had affected the activities for concluding the building agreements. By analyzing the survey results, the following were argued to be the keys for promoting consensus building for building agreements; ①attractiveness of the local community, ②leadership type, ③motivation for achieving the goal, ④conditions of housing environment, ⑤ support from the local authorities. It was proposed that it's necessary to have controls with spaces with flexibility as well as utilization of neighborhood organization. 住民自らの手で住環境を管理していく「建築協定」には大別して，地区住民が自主的に締結した「全員合意による協定」（合意協定）と，事業主が分譲前に締結した「住民合意をふまえない協定」（一人協定）とがある。実際には，住民合意をふまえない一人協定を締結した地区が大半であるため，協定運用上で様々な問題点を残している。また，一人協定地区においても更新時期をむかえた地区が多くなり，建築協定が定着した段階での新たな政策展開が必要となってきている。本研究は，このような建築協定制度の問題点を改善して，住民参加による住環境形成活動を有効に機能させるような合意形成手法のあり方を検討したものである。そのために，成熟化過程にある住宅団地での協定運用の実態を把握するとともに，建築協定が有効期限に達した地区での更新状況を明らかにした。さらに，住民合意をふまえて建築協定を締結・更新するための合意形成活動の実態を把握した。そして，これらの実態から地区住民の合意形成を促進するための基本条件を検討した。　その結果，一人協定地区においても協定の有用性が評価され，多くの地区で更新に成功していることがわかった。しかも，更新を機会に地区の実情に応じて，協定内容や協定区域を変更するなど，様々な対応がなされていることが把握された。さらに，建築協定に対する合意形成活動には，協定の締結背景や地区の環境条件などにより特徴があることを明らかにした。一人協定は規範形成の上で重要な役割を果たしているものの，更新時には合意手続き作業に多くの時間を要しており，住環境の同質性や，規範意識の存在などが更新活動を左右する要因となっていた。こうした実態から，建築協定に対する合意形成を促進するためには，①地区の魅力度②リーダーシップ・タイプ，③目標達成への動機つけ，④住環境の条件，⑤行政側の支援などの面での対策が重要であることを論じた。また住民組織の活用とともに，非計画性を付与した建築的な〈しかけ〉も必要であることを提案した。